Expression of stress responsive genes enables Limosilactobacillus reuteri to cross-protection against acid, bile salt, and freeze-drying - Liu, Zhenzhen; Zhao, Xiao; Bangash, Hina Iqbal (Frontiers in Microbiology, 2024)
Limosilactobacillus reuteri effectively colonizing the gut, secretes antimicrobial compounds and strengthens immune system function. Considering these health benefits, increasing its stress assessments efficiency could improve its commercial viability. For this purpose, the resistance of L. reuteri FP41 to acid, bile salts, and freeze-drying was examined. The findings showed that strain FP41 demonstrated a strong resistance to acid/bile salt stresses. The transcriptome revealed a significant upregulation of various stress response genes, including those related to membrane integrity, glutamine metabolism, OsmC family protein, ABC transporters, and chaperonin. Subsequent research demonstrated that overexpression of three stress response-specific proteins, including glutamate decarboxylase GatD, osmotically induced bacterial protein OsmC, and membrane protein component CsbD, significantly increased the survival rate of L. reuteri Z204 under acid/bile salts stress.Notably, overexpression of the OsmC, CsbD, and GatD proteins also enhanced the survival of L. reuteri after freeze-drying. The development of a unique crossprotection method is highlighted in this study, that might significantly increase cellular resistance to acid, bile salts, and cold stresses. This finding could significantly impact the way that L. reuteri is employed in industrial manufacturing processes.